2023
DOI: 10.1007/s13760-023-02188-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective survey of patients with hereditary transthyretin-mediated (hATTR) amyloidosis treated with patisiran in real-world clinical practice in Belgium

Abstract: Introduction Hereditary transthyretin-mediated (hATTR) amyloidosis, a genetic disease caused by mutations in the transthyretin gene, leads to progressive sensory and autonomic neuropathy and/or cardiomyopathy and is associated with renal and ophthalmologic manifestations and a poor prognosis. Methods This is a retrospective study based on data collected from the medical records of patients with hATTR amyloidosis treated with patisiran between 01 July 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…Patisiran is also approved to be effective at reducing polyneuropathy for hATTR patients after liver transplantation (Schmidt et al, 2022). A real-world clinical study with Belgium hATTR patients showed a similar therapeutic response for altering the expected disease progression in most patients (De Bleecker et al, 2023).…”
Section: Patisiranmentioning
confidence: 99%
“…Patisiran is also approved to be effective at reducing polyneuropathy for hATTR patients after liver transplantation (Schmidt et al, 2022). A real-world clinical study with Belgium hATTR patients showed a similar therapeutic response for altering the expected disease progression in most patients (De Bleecker et al, 2023).…”
Section: Patisiranmentioning
confidence: 99%
“…Hereditary transthyretin amyloidosis (ATTRv) is a rare, autosomal dominant, multisystem disease caused by mutations in the transthyretin (TTR) gene ( 1 ). The main features of the disease are progressive sensory-motor and autonomic neuropathy and cardiomyopathy ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%